Approaches to the views of Neuquén police workers, in relation to masculinities, diversities and violence (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
The following article aims to investigate the perspectives of police workers in the province of Neuquén regarding masculinities, gender and diversity.The article is based on the elaboration and diffusion of an anonymous survey (2022) directed specifically to men who transit or transited the police institution, which allows us to know certain characterizations that are perceived on the proposed topics.On the other hand, comparative analyzes were carried out with the results of anonymous surveys carried out in previous years in heterogeneous groups of men and women who make up the police institution.
Keywords: Police workers; Masculinities; Subjetivities; Diversities; Violence